Sistem Informasi Penjadwalan Mata Kuliah Pada Jurusan Teknik Elektro Fakultas Teknik Universitas Riau - Nur Hidayah Muzaeni; Salhazan Nasution (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Courses timetabling is one of the most important administrative activities that is always carried out before entering the beginning of the semester. The courses timetabling at the Electrical Engineering Department actually uses computers, but it has not been used optimally. The timetable for the Electrical Engineering Department is made with the help of the Microsoft Excel program so that scheduling and detecting conflicting schedules is difficult. the solution to this problem is a web-based course timetabling information system that can be accessed via a computer, laptop or smartphone and can also detect conflicting timetable so that this system can help facilitate administrative staff in timetabling and make it easier for lecturers to get information about course timetable anywhere and anytime. functionality testing has been carried out using the black box testing method. Based on the results of the Black Box test, this Course timetabling Information System can functionally be used properly and produce results as expected. Keywords: Course timetabling Information System, web application, Black Box Testing